Hubungan Kadar Timbal (Pb) Darah Dengan Hipertensi Pada Pengemudi Ojek - Chendrasari, Julian; Lestari, Indah Widya; Ilona, Florinda; Digambiro, Reza (Jurnal Biomedika dan Kesehatan, 2024)
Background Hypertension is a disease that is a major health problem in developed and developing countries and is the number one cause of death in the world every year. The causes of hypertension can be divided into genetic and environmental factors. One of the causes of hypertension from environmental causes is exposure to lead. This study aims to determine the relationship between blood lead levels and hypertension. Methods The design of this research is descriptive research with laboratory analysis using a cross-sectional approach. Sample selection using a purposive sampling method. The research sample was online motorcycle taxi drivers aged >35 years, with a minimum of 1 year as an online motorcycle taxi driver. Research samples were taken at the Faculty of Medicine, Trisakti University in September 2022. Laboratory examinations were carried out at the Prodia clinical laboratory, in Jakarta. Results Of the 133 samples examined, high lead levels were found in 20 respondents (15%) and low lead levels in 113 respondents (85%). High lead levels were found in 7 respondents who had hypertension and 13 respondents with normal blood pressure. The chi-square statistical test value shows a p-value = 0.260. Conclusions Blood lead levels do not have a significant relationship with blood pressure in motorbike taxi drivers.